Automatic proximal airway volume segmentation using optical coherence tomography for assessment of inhalation injury. Issue 1 (July 2019) - Miao, Yusi; Choi, Jae Hyek; Chou, Li-Dek; Desai, Vineet; Roberts, Teryn R.; Beely, Brendan M.; Wendorff, Daniel S.; Espinoza, Mark; Sieck, Kyle; Cancio, Leopoldo C.; Brenner, Matthew; Batchinsky, Andriy I.; et al.
Abstract : BACKGROUND: Acute respiratory distress syndrome (ARDS) is a severe form of acute lung injury with a mortality rate of up to 40%. Early management of ARDS has been difficult due to the lack of sensitive imaging tools and robust analysis software. We previously designed an optical coherence tomography (OCT) system to evaluate mucosa thickness (MT) after smoke inhalation, but the analysis relied on manual segmentation. The aim of this study is to assess in vivo proximal airway volume (PAV) after inhalation injury using automated OCT segmentation and correlate the PAV to lung function for rapid indication of ARDS. METHODS: Anesthetized female Yorkshire pigs (n = 14) received smoke inhalation injury (SII) and 40% total body surface area thermal burns. Measurements of PaO2 -to-FiO2 ratio (PFR), peak inspiratory pressure (PIP), dynamic compliance, airway resistance, and OCT bronchoscopy were performed at baseline, postinjury, 24 hours, 48 hours, 72 hours after injury. A tissue segmentation algorithm based on graph theory was used to reconstruct a three-dimensional (3D) model of lower respiratory tract and estimate PAV. Proximal airway volume was correlated with PFR, PIP, compliance, resistance, and MT measurement using a linear regression model. RESULTS: Proximal airway volume decreased after the SII: the group mean of proximal airway volume at baseline, postinjury, 24 hours, 48 hours, 72 hours were 20.86 cm 3 (±1.39 cm 3 ), 17.61 cm 3 (±0.99 cm 3 ), 14.83 cm 3 (±1.20 cm 3 ), 14.88 cm 3 (±1.21 cm 3 ), and 13.11 cm 3 (±1.59 cm 3 ), respectively. The decrease in the PAV was more prominent in the animals that developed ARDS after 24 hours after the injury. PAV was significantly correlated with PIP ( r = 0.48, p < 0.001), compliance ( r = 0.55, p < 0.001), resistance ( r = 0.35, p < 0.01), MT ( r = 0.60, p < 0.001), and PFR ( r = 0.34, p < 0.01). CONCLUSION: Optical coherence tomography is a useful tool to quantify changes in MT and PAV after SII and burns, which can be used as predictors of developing ARDS at an early stage. LEVEL OF EVIDENCE: Prognostic, level III. Abstract : Supplemental digital content is available in the text.